The interest of Jamaican trained undergraduate physiotherapy students to provide physiotherapy services to older adults once qualified as a physiotherapist: a descriptive study - Sonja K.P. Williams (Caribbean Medical Journal)
Objective: To determine the interest of undergraduate physiotherapy students in Jamaica in providing physiotherapy services to older adults upon graduation. Understanding such interest in this student population becomes necessary as the older Jamaican adult population is growing rapidly (Statistical Institute of Jamaica, STATIN), and such interest has never been investigated. This study also explores the differences between students’ interest and some personal characteristics. Methods: The data used to produce this paper were part of a larger data set for a larger cross-sectional study, which had not previously been published. Ethical approval was granted by the Mona Campus Research Ethics Committee (MCREC). Convenience sampling was used in this census survey to recruit students for this study. All students registered in the physiotherapy undergraduate programme, were invited to participate in the study. Those accepting the invitation gave written consent and completed the data collection instruments. Those on leave of absence would not have been registered for any course in the programme of study and were therefore excluded. Results: 110 out of 129 students participated. The response rate was 85%. Of the 110 students, 46% (n=51) expressed an interest in providing physiotherapy services to older adults once they qualified as a physiotherapist. The interest in providing physiotherapy services to older adults after graduation was more likely to be seen among students who had not yet completed their gerontology course content (p = .005), who had completed fewer placements (p = 0.04), and who had not provided physiotherapy treatment to infirmed older adults (p = 0.021). There was insignificant evidence of a difference in interest between males and females (p = 0.71). Conclusion: Many students expressed interest in providing physiotherapy services post-graduation. Completing the gerontology course and exposure to infirmed older adults while on clinical placement, appear negatively to influence such interest for these Jamaican-trained physiotherapy students. The implications of these findings were discussed in relation to the Jamaican-trained physiotherapy students.